(untitled) - Simpson, Ted (Boston, Mass., 2006)
This full-color book combines Course Technology's proven Microsoft Windows Server 2003 and Windows XP Professional content in one volume for those who teach these two popular subjects in a single course.
Keywords: Windows xp (computer programs),Windows XP